2010
DOI: 10.1177/0013124510380721
|View full text |Cite
|
Sign up to set email alerts
|

Deficit Thinking and the Effective Teacher

Abstract: This research was a qualitative study of 10 elementary school teachers working with predominantly African American students in a large urban school district. The primary focus of this study was to analyze the teachers' perceptions of their African American students. The hope is that the data presented in this study will initiate trends that assist in effectively preparing teachers to attain successful outcomes with African American students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 8 publications
1
17
0
1
Order By: Relevance
“…Through relevant content the learning is made interesting and appealing by embedding it within the students' cultural frames of reference. This can be achieved by valuing the whole child, adjusting the curriculum, using culturally appropriate behaviour management techniques, alternative modes of assessment, as well as ensuring that learning does not remain confined to the four walls of the classroom (Lewthwaite and McMillan, 2010;Lewthwaite et al, 2013;Nakata, 2011;Osborne, 2001;Walker, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through relevant content the learning is made interesting and appealing by embedding it within the students' cultural frames of reference. This can be achieved by valuing the whole child, adjusting the curriculum, using culturally appropriate behaviour management techniques, alternative modes of assessment, as well as ensuring that learning does not remain confined to the four walls of the classroom (Lewthwaite and McMillan, 2010;Lewthwaite et al, 2013;Nakata, 2011;Osborne, 2001;Walker, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Ahram, Fergus, & Noguera, 2011, p. 2247 Culturally deficit thinking is represented by school staffs' characterization of lowincome students and/or CLD students including ELL students as psychologically abnormal. Deficit thinking blames school failure on the students, their parents, background and families (Walker, 2011). All students are compared academically and behaviorally to white middle class students.…”
Section: Culturally Deficit Thinkingmentioning
confidence: 99%
“…Research has also shown that teachers' instructional choices are sometimes influenced by colorblind or biased ideology (Bennett, 2012;Love & Kruger, 2005;Natesan & Kieftenbeld, 2013;Siwatu, 2011;Song, 2006;Walker, 2011). When teachers use a curriculum that is not culturally relevant to students of color, those students' academic ability might not be optimized.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Love and Kruger (2005) urge teachers to reflect on their own beliefs about the community in which they teach. Teachers must examine their expectations of students with a critical lens so that they can push back against deficit or racist beliefs (Atwater, 2008;Howard, 2003;Nelson & Guerra, 2014;Walker, 2011).…”
Section: Ladsonmentioning
confidence: 99%
See 1 more Smart Citation